2001
DOI: 10.1106/e7wd-x288-xfk7-6e90
|View full text |Cite
|
Sign up to set email alerts
|

Foaming of Thermoplastic Elastomers with Water

Abstract: We present results on foaming of a thermoplastic elastomer (TPE) using water as the physical blowing agent. The TPE is a blend of polypropylene and fully crosslinked EPDM rubber made by a dynamic vulcanization process. The influence of the blowing agent content, and the processing conditions on foam density, cell nucleation, and foam structure are discussed. A brief discussion about the similarities and the differences between foaming in homopolymers and in TPEs is also included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…However, attempts to foam pure PE or PP with water were unsuccessful. Sahnoune 21 and Snyder 22 describe the use of water as a blowing agent for foaming TPEs. Matuana and Mengeloglou 23 used moisture as a foaming agent in the manufacture of rigid poly(vinyl chloride) (PVC)/wood-flour composite foams.…”
Section: Introductionmentioning
confidence: 99%
“…However, attempts to foam pure PE or PP with water were unsuccessful. Sahnoune 21 and Snyder 22 describe the use of water as a blowing agent for foaming TPEs. Matuana and Mengeloglou 23 used moisture as a foaming agent in the manufacture of rigid poly(vinyl chloride) (PVC)/wood-flour composite foams.…”
Section: Introductionmentioning
confidence: 99%
“…Cells are more closed at high screw speeds, which implicate shorter residence time in the die and this factor accelerates the freezing of cell structure. Furthermore, the competition between cell nucleation and cell growth exists so that a large part of gas is used for nucleation instead of growth when a large number of nuclei are created at a high screw speed which is corresponding to a high pressure drop [14,38]. As seen in Table 5, higher screw speed gave the foam lower void fraction, smaller average cell size and higher cell density.…”
Section: Effect Of Screw Speed On the Cell Morphologymentioning
confidence: 87%
“…Dutta and Cakmak [13] studied foaming of PP/ EPDM blends using chemical blowing agents. Sahnoune [14] and Snyder [15] described the usage of water as a blowing agent for foaming TPEs. Kiatkamjornwong, Thinakorn, and Tosa [16] studied the effect of natural rubber (NR) concentration on foam structures and properties under various conditions for high density polyethylenenatural rubber blends and found that when the NR content was more than 30%, the cell shape distorted.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to dissolve a certain high amount of water into the polymer matrix, which is necessary for producing low‐density foams, under prevailing extrusion foaming conditions. If water is not completely dissolved in polymer matrix, the undissolved water droplets will lead to processing instability, non‐uniform cellular morphology, and severe foam shrinkage . To overcome this challenge, the idea of introducing “water carrier” was developed.…”
Section: Introductionmentioning
confidence: 99%